The complexity vision and the teaching of economics - Colander, David C. (Cheltenham [England] ; Northampton, MA : Edward Elgar, 2000)
This work focuses on the implications of the complexity vision, such as held by economists at the Santa Fe Institute, for the teaching of economics. This complexity vision suggests that answers to questions such as how do markets develop and how do they evolve need to be approached head on. Complexity economics is beginning to do just that. The focus of this book is not on the grand theories, or technical aspects, of complexity. Instead it is on the teaching of economics. It asks the question: how would the teaching of economics change if complexity is taken seriously? An outstanding group of contributors, including Brian Arthur, Buz Brock and Duncan Foley, provide interesting and provocative answers to that question in a non-technical and highly accessible style. It is a book that should be read by all those teaching economics, as well as those who are interested in where the complexity revolution in science might be leading.
Includes bibliographical references and index.
rpm 29/10/13
Loans
Keywords: Complexity (Philosophy); Economics -- Study and teaching